Kedudukan Direktorat Jenderal Hak Kekayaan Intelektual (HKI) dalam Perlindungan Hak Cipta Lagu - Yoaneta Spiridiana Sorowea; I Nyoman Sukandia; Desak Gde Dwi Arini (Warmadewa Press, 2024)
Copyright is the exclusive right of creators to regulate the ownership and distribution of their work. In Indonesia, the Directorate General of Intellectual Property Rights (IPR) plays a role in ensuring that copyright is protected and enforced, including in the context of music or songs. The focus of this research is to evaluate how the law, specifically Law Number 28 of 2014 on Copyright, provides legal protection to songs. In addition, the research also examines the role of the Directorate General of Intellectual Property in providing protection to song copyrights. The research method used is the normative method. The results showed that in the case of the song